Nurturing Corporate Culture With the Wisdom of the Gita - A Gateway for Good Governance - Kumar, Raj; Chandel, Kulbhushan (Prabandhan: Indian Journal of Management, 2010)
In the recent decades, especially in the post globalised era, the issues relating to Corporate Governance have assumed a great significance and concern. The crisis of credibility and confidence during the early years of the new millennium has been created by the frauds, scandals and failures of several large corporations in the various countries of the world. The major corporations which have created a havoc in corporate world include Enron, Adelphia, Arthur Anderson, Parmalat, Tyco, Global Crossing, WorldCom unconditionally and the recent Satyam scam in India. This has caused people around the world to seriously question the corporate culture, ethics and values of business organizations and its executives, auditor and leaders also. These series of corporate scams and scandals are taking place in the presence of strict laws, rules and regulations such as Sarbanes-Oxley Act 2002 in America, the combined code (1998), which was derived from the Cadbury committee report (1992), Hamphel committee report (1995) and Greenbury committee report (1995) in U.K. Even in India, the corporate world could not remain indifferent to the developments that have taken place in America and U.K. and in other countries of the world. Consequently, various committees such as Rahul Bajaj committee (1997), Kumar Mangalam Girla Committee (1999),Naresh Chandra committee 2002, Narayan Murthy committee (2003) and Dr. J.J. Irani committee report (2005) on Corporate Governance made many recommendations for good governance. In-spite of all these rules regulations, codes and recommendation, the infamous Satyam scam was unearthed in India in January 2009.